Posterior vaginal wall cyst of Mullerian origin: a case report - Samal, Sunita; Mahapatro, Akshaya; Poorkodi, Barathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cystic lesions of vagina are relatively uncommon and an incidental finding during routine gynaecological examination. Mullerian cysts are congenital cysts of vagina, usually reported during childbearing age group. These cysts mostly arise at the level of cervix and extend anteriorly in relation to bladder, but very rarely they may also extend posteriorly. This is a rare case of posterior vaginal wall cyst of Mullerian origin. A 36-year-old multi para (P2L2 both SVD), presented with a mass descending through vagina since 2-3 months. Pelvic examination revealed a 5x5 cm cystic mass arising from the posterior vaginal wall. Complete excision of the cyst was done. The cyst was filled with chocolate coloured material and histopathology confirmed a Mullerian cyst.